Wastewater as Nutrient Enhancer and Moisturizer for Compost Production : A Review - Abu Zahrim, Yaser; Junidah, Lamaming (CRC PRESS, 2023)
Industrial wastewater disposal exacerbates environmental issues not just at the national level, but also globally. These wastes are phytotoxic, but they also include a high amount of water, organic matter, and nutrients that can be exploited as nutrient enhancers and moisturizers in the composting process. Recent research on the use of selected wastewater is reviewed, with a focus on the use of wastewater content as a nutritional enhancer and moisturizer that can be utilized directly and recycled, as well as the possibility of reducing load in wastewater treatment plant. The wastewaters from the industries of oil mill, olive mill, alcohol or molasses distillery, swine, composting facilities, and monosodium glutamate are among the wastewaters mentioned in the review. The wastewater was incorporated, mixed, and absorbed by the solid substrate such as pressmud, food waste, grape marc, animal manures, green waste, grass clippings, mushroom waste, and rice husk during the composting process. The increasing nutrients found in this effluent vary from 1.05% to 6.1% (N), 0.06% to 2.8% (P), and 0.06% to 12.43% (K), proving their potential as nutrient enhancer.